The Influence of Job Stress on Employee Turnover Intention Mediated by Job Satisfaction - Wicaksana, Thiyo; Jihadi, Muhammad; Novianti, Khusnul Rofida (Universitas Muhammadiyah Malang, 2024)
The purpose of this research is to determine and analyze job stress, job satisfaction, and employee turnover intention levels, the influence of job stress on employee job satisfaction, the influence of job stress on turnover intention, the influence of satisfaction on turnover intention, and whether job satisfaction can mediate the influence of job stress on turnover intention. This research was conducted on J&T Malang City employees with 100 respondents using non-probability sampling. Data collection uses questionnaires. The data analysis technique uses path analysis and the SPSS 25 program. The results of this study show that job stress shows low results, high job satisfaction, and low turnover rates. There is an influence of job stress on turnover intention, job stress has no effect on job satisfaction, job satisfaction has no effect on turnover and job satisfaction does not mediate job stress on turnover intention.